Performance Evaluation Using the Malcolm Baldrige Criteria for Performance Excellence in the AVP Production Department of PT. XYZ - Nikita Dinda Purnamasari; Iriani Iriani (Universitas KH. Abdul Chalim Mojokerto, 2025)
In the era of intense global competition, companies must ensure that all organizational elements function optimally and align with strategic goals. PT. XYZ, a seafood processing company under X Group, faces challenges in achieving production targets, with an average realization of 59% in the first half of 2024. High employee turnover (13%) and dissatisfaction with wages and working conditions have been identified as key issues impacting performance. These challenges underscore the need for a comprehensive evaluation to improve productivity and achieve performance excellence. This study aims to evaluate the performance of the AVP production department at PT. XYZ using the Malcolm Baldrige Criteria for Performance Excellence (MBCfPE). Data collection involved distributing questionnaires to 30 respondents, including managers, supervisors, Rnd, Purchasing, and employees, followed by validity and reliability testing using Smart PLS software. The evaluation results indicate that the AVP production department achieved a total score of 814.53, placing it in the